EVALUATION OF PORK QUALITY AT THREE TRADITIONAL MARKETS IN DENPASAR CITY, BALI - Resman, Martin Pedro Krisenda; Nurmayani, Rima; Nadira, Laras Ayu; Gani, Vinensia Ghona; Mukti, Made Beratha; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023DO - 10.24843/bulvet.2023.v15.i04.p04, 2023)
People's need for animal protein is very high. One source of animal protein that is quite popular is pork. Pigs are one of the livestock that are quite a lot kept by the people of Indonesia, especially livestock that are kept large by the Balinese people. The purpose of this study was to develop the quality of pork in three traditional markets in Denpasar, Bali. The pork samples examined were obtained from traditional markets in the Denpasar area, such as the Sanglah market, Pemogan market, and Jimbar Jaya Renon market. Inspection of quality is carried out through subjective tests (color, consistency and texture) and objective examinations on meat include examination of pH determination, Water Holding Capacity, Water Content, and Total Bacterial Plate Number Test (ALTB) as a Microbiological Test. The results of subjective evaluation of pork from three Denpasar Traditional Markets all have an average of pale red color (score 1), smell of fresh blood (score 1), soft consistency (score 1), and smooth texture (score 1). As for the objective test, at Sanglah Market, the average pH test was 6.5, water holding capacity was 83.6%, water content was 73.7%, and ALTB was 412.33x10 3 cfu/g; at Pemogan Market pH 6.3, Water Holding Capacity 81.5%, Water Content 72.7%; and ALTB 515.66x 10 3 cfu/g, Jimbar Jaya Renon Market tested for pH 6.37, water holding capacity 90.4%, water content 75.01%, and ALTB 528x10 3 cfu/g. It can be said that the quality of pork sold in the three traditional markets of Denpasar City is in accordance with the Indonesian National Standard (SNI) and is still fit for consumption. It is recommended that pork traders in the traditional markets of Denpasar City continue to carry out sanitation and hygiene properly and correctly so that the quality of pork is maintained.